Identifikasi Pemborosan dengan menggunakan Cycle Time pada Plant 1 di PT. X - Emmanuelle Naomi Eleonora Njoradi; I Gede Agus Widyadana (Jurnal Titra, 2022)
This company has several production lines and make to order systems where production is conducted after consumer orders are received. The company uses formula calculations to find the estimated time required to complete each order. The result of production process time is used for decision making of selling price and time of order completion. Thus, it is important to do cycle time monitoring so this company can discover the cause of non-value added. This research was conducted by performing observation to obtain cycle time data. The retrieved data are processed to discover waste analysis. Improvements are given to each root of the problem that has the highest waste value. Those values belong to several activities such as picking up wood, waiting because the heating sheet is not ready, picking up tools, talking, and waiting because the expand machine is still in use. The proposed improvements for those activities are to make inventory buffers, update working instructions, alter operator tasks, expand machine training, reevaluate production targets, and provide trolly tools.